The Strengthening Local Wisdom In Stunting Prevention With Sauropus Androgynous Leaves Among Toddlers - Fitrianingsih, Nining; Rowi, Armein Sjuhary; Agus, Agus; Yanti, Tisna; Rizki, Eni; Mulyati, Tri; Bustomi, Bustomi; Elpinaria, Elpinaria; Suryaman, Ratih (Universitas Respati Yogyakarta, 2025)
Stunting during the crucial stages of early childhood represents a major public health issue worldwide. One way to prevent stunting is by using katuk (Sauropus androgynous) leaves as part of a balanced diet. Nursing practitioners are essential in preventing and managing stunting, particularly in communities affected by widespread malnutrition. This research contributed to strengthen local wisdom in stunting prevention by utilizing Sauropus androgynous leaves among toddlers. The study is pre-experimental with one group pre and post-test design. The sampling method uses total sampling of 24 toddlers (aged 12-50 months old). Respondents were given an intervention in the form of taking Sauropus androgynous leaves juice which was given once a day for 3 days alternately in a week with an amount of 250 cc juice each time. To prepare the juice, it is necessary to wash 100 grams of Sauropus androgynous leaves thoroughly. Subsequently, blend the leaves with 250 cc of water and 50 grams of pineapple. Finally, strain the mixture to achieve a smoother consistency. Data measurement was carried out by measuring height based on age using a Stature meter (growth chart) in the pretest and posttest. Data were analyzed using the Wilcoxon sign rank test with a significance level of Î± = 0.05. The results of the study showed that the average normal z score value before taking Sauropus androgynous leaves juice was 66.7%. After intervention with Sauropus androgynous leaves juice, there was an increase in the number of normal z scores to 83.3%. The results of the Wilcoxon signed rank test hypothesis showed the Sig value = 0.046 and there was a significant difference in Z Score values in toddlers aged 12-50 months old before and after taking Sauropus androgynous leaves juice.